Compact generation scheme of path–frequency hyperentangled photons using 2D periodical nonlinear photonic crystal - Chen, Yang-He; Ji, Bo; Li, Nian-Qin; Jiang, Zhen; Li, Wei; Li, Yu-Dong; Feng, Liang-Sen; Wu, Teng-Fei; He, Guang-Qiang (Chinese physics B, 2023)
Hyperentanglement is a promising resource for achieving high capacity quantum communication. Here, we propose a compact scheme for the generation of path–frequency hyperentangled photon pairs via spontaneous parametric down-conversion (SPDC) processes, where six different paths and two different frequencies are covered. A two-dimensional periodical χ (2) nonlinear photonic crystal (NPC) is designed to satisfy type-I quasi-phase-matching conditions in the plane perpendicular to the incident pump beam, and a perfect phase match is achieved along the pump beam’s direction to ensure high conversion efficiency, with theoretically estimated photon flux up to 2.068 × 10 5 pairs⋅s −1 ⋅mm −2 . We theoretically calculate the joint-spectral amplitude (JSA) of the generated photon pair and perform Schmidt decomposition on it, where the resulting entropy S of entanglement and effective Schmidt rank K reach 3.2789 and 6.4675, respectively. Our hyperentangled photon source scheme could provide new avenues for high-dimensional quantum communication and high-speed quantum information processing.